ANALISIS SIFAT FISIK DAN SIFAT MEKANIK BATU KARANG DI KUPANG - Letto, Robby; Pell, Yeremias M.; Bunganaen, Wenseslaus (Universitas Nusa Cendana, 2023)
Coral is a natural potential that has not been exploited on a large scale and in this study aims to analyze the physical properties and mechanical properties of coral in Kupang city. and useful for development activities to be safer and smoother. Tools and materials used to analyze the physical properties and mechanical properties of coral such as m esin uji t ekan m ortal, g erinda, m ata p isau p otong keramic, m ata gerinda p smear , betta esi(Ragum), jfigure sfunnel. , the material is in the form of Coral. And all calculations against the compressive strength of the rock.